Agua de coco como diluyente de semen porcino a diferentes temperaturas sobre la respuesta reproductiva con inseminación artificial en cerdas - Farías Rodríguez, Lucía Eloísa (2017)
The research was studied in the herd porcine teaching and research unit and in the reproduction biotechnology laboratory, where a comparison of two commercial diluents BTS (Beltsville Thawing Solution) and another natural like coconut water (Cocus nucifera) both diluents with two different insemination temperatures at 37 ° C and 17 ° C, 16 multiparous sows were selected at random for the respective treatments 4 sows for each treatment, DCA was used (completely randomized design) with bifactorial arrangement with four replicates, them was applied a Chi-square test for non-parametric variables, the variables to be analyzed were motility, agglutination, sperm mortality, fertility, total number of piglets born and live births. In the microscopic evaluation there was no significant difference (p> 0.05) between each of the treatments with BTS at 37 and 17ºC and coconut water at 37 and 17ºC, in addition, the results obtained in fertility did not find significant difference (p> 0.05 ) BTS and coconut water 37 ° C 100% and at 17 ° C 75%. In total born piglets there is a significant difference between 37 ° C and 17 ° C, which at 37 ° C (p> 0.05) with a mean of 11.50 and 17 ° C with 7.67. In live births, no significant difference was observed at 37 ° C. BTS reported 8.25 (± 2.06), and coconut water averaged 10.5. With diluent coconut water at 17 ° C an average of 6.67, with BTS at 17 ° C an average of 8.67. The results suggest that coconut water can be used as a diluent.